Penerapan Konseling Individu dengan Teknik Congnitive Restructuring untuk Mereduksi Pola Pikir Negatif Narapidana Pembunuhan - Aghniya Ahsana; Abdur Razzaq; Zhila Jannati (Journal of Society Counseling, 2023)
Negative thought patterns can result in individuals feeling like they have failed, lacking self-confidence, remembering a dark past, considering this as bad luck, giving up hope and having difficulty solving problems on their own. Researchers are trying to provide individual counseling guidance to reshape positive thinking patterns in client "A", a murder convict at LPKA Class 1 Pakjo Palembang. The aim of the research is to determine the description of the negative thought patterns experienced by murder convicts at LPKA Class 1 Pakjo Palembang before and after implementing individual counseling using cognitive restructuring techniques and applying individual counseling using cognitive restructuring techniques to reduce the negative thinking patterns of murder convicts. The approach used in this research is a qualitative approach with a case study research method. The subject, namely client "A", comes from Gandus District, 20 years old, convicted of murder, sentenced to 8 years and 6 months. Data collection techniques through observation, interviews, documentation. Meanwhile, the data analysis techniques used are pattern matching, explanation, time series analysis. The results of the research show that (1) The negative thought pattern of client "A" shows an attitude of feeling like a failure, giving up hope, often blaming others, likes to be alone, suffering from mental or physical illness, unable to accept change, unsure of business opportunities, feels that he is experiencing Failure results in low self-esteem. (2) The cognitive restructuring technique is carried out in 4 meetings lasting 60 minutes. The first meeting, observing "negative thoughts" influenced thoughts of not blaming yourself. Second, the client has the courage to try new things but avoids relationships with other people. Third, the counselee accepts reality, uses himself, does not get lost in sadness. Fourth, carry out follow-up to see the progress of counseling at the last meeting so that the formation of client "A"'s negative thought pattern is reduced and controlled into a positive thought pattern. (3) As well as the description of negative thought patterns in clients showing changes in being serious about achieving their desires, reducing attitudes of despair and daring to try without fear of failure. In this case, the client begins to show calmer mental health. The client begins to let go of the burden of regret he has suffered all this time.